Perbandingan Usability Pada Learning Management System Moodle dan Edmodo Dengan Menggunakan Metode Heuristic Walkthrough (Studi Pada SMKN 8 Malang) - Hardy Padmayudha Nugraha; Admaja Dwi Herlambang; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Edmodo and Moodle are systems which can be use in learning management. These two systems are popular in middle school and higher educational level. But, not all of the instructors know how to operate these systems caused by complicated design that have an impact in usability and learnabililty aspect. In order for usability reached properly, these two systems need to be evaluated with cognitive walkthrough and heuristic evaluation, six evaluators and comparative research. There are 15 problems in Moodle and seven problems in learning ability using the cognitive walkthrough method. For research with heuristic evaluation methods, there are 16 problems in Moodle with the highest frequency is H-8 (Aesthetic and minimalist design), as well as total severity rating is 2.50. As for the heuristic evaluation method in Edmodo, there were 15 problems with the highest frequencies are: (1) H-1 (System status visibility); (2) H-2 (Suitability between the system and the real world); (3) H-4 (Consistency and standards); (4) H-7 (Flexibility and efficiency of use); (5) H-8 (Aesthetic and minimalist design); and (6) H-10 (Help and documentation) as many as two for each principle, and the total average number of severity rating is 2.30. Edmodo is recommended because of it's user interface design that can be easily recognized by user. While, Moodle is recommended for an expert user that needs a LMS that has complex feature.